Genus_Ruminococcus and order_Burkholderiales affect osteoporosis by regulating the microbiota-gut-bone axis - Li, Ning; Wang, Haiyang; Pei, Huan; Wu, Yueying; Li, Lei; Ren, Yu; Wang, Si; Ma, Yuan; Luo, Miao; Yuan, Jiali; Li, Lvyu; Qin, Dongdong (Frontiers in Microbiology, 2024)
Background: This study aimed to clarify the relationship between the gut microbiota and osteoporosis combining Mendelian randomization (MR) analysis with animal experiments. Methods:We conducted an analysis on the relationship between differential bacteria and osteoporosis using open-access genome-wide association study (GWAS) data on gut microbe and osteoporosis obtained from public databases. The analysis was performed using two-sample MR analysis, and the causal relationship was examined through Inverse Variance Weighting (IVW), MR Egger, weighted median, and weighted mode methods. Bilateral oophorectomy was employed to replicate the mouse osteoporosis model, which was assessed by micro computed tomography (CT), pathological tests, and bone transformation indexes. Additionally, 16S rDNA sequencing was conducted on fecal samples, while SIgA and indexes of IL-6, IL-1β, and TNF-α inflammatory factors were examined in colon samples. Through immunofluorescence and histopathology, expression levels of tight junction proteins, such as Claudin-1, ZO-1, and Occludin, were assessed, and conduct correlation analysis on differential bacteria and related environmental factors were performed. Results: A positive correlation was observed between g_Ruminococcus1 and the risk of osteoporosis, while O_Burkholderiales showed a negative correlation with the risk of osteoporosis. Furthermore, there was no evidence of heterogeneity or pleiotropy. The successful replication of the mouse osteoporosis model was assessed, and it was found that the abundance of the O_Burkholderiales was significantly reduced, while the abundance of g_Ruminococcus was significantly increased in the ovariectomized (OVX)-mice. The intestinal SIgA level of OVX mice decreased, the expression level of inflammatory factors increased, barrier damage occurred, and the content of LPS in the colon and serum significantly increased. The abundance level of O_Burkholderiales is strongly positively correlated with bone formation factors, gut barrier indicators, bone density, bone volume fraction, and trabecular bone quantity, whereas it was strongly negatively correlated with bone resorption factors and intestinal inflammatory factors, The abundance level of g_Ruminococcus shows a strong negative correlation with bone formation factors, gut barrier indicators, and bone volume fraction, and a strong positive correlation with bone resorption factors and intestinal inflammatory factors. Conclusion: O_Burkholderiales and g_Ruminococcus may regulate the development of osteoporosis through the microbiota-gut-bone axis.